2018
DOI: 10.1186/s40497-018-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Social enterprises in the Indian context: conceptualizing through qualitative lens

Abstract: Adopting an inductive theory building approach through qualitative research methodology of data collection and analysis spread across six months, followed by inter-rater reliability testing using quantitative technique, this empirical study researches the meaning of the 'social enterprise' construct in the Indian context, and develops a conceptual framework that represents the construct. This sets an orientation needed for aspiring social entrepreneurs and social entrepreneurship researchers to ease out their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 54 publications
0
11
0
2
Order By: Relevance
“…It should also be noted that unlike registered societies, cooperatives, or companies, 'social enterprise' does not exist in the Indian legal framework as a company format for incorporation (registration). Therefore, different actors in the social entrepreneurship ecosystem of the country, tend to consider those enterprises as social enterprise which combine the logic of market orientation and social value creation for achieving a social mission, irrespective of the legal identity of the enterprise; be it a cooperative, a trust, a society, a section 8 company, or a private limited company (Sengupta and Sahay, 2018).…”
Section: New and Renewable Energy Social Entrepreneurship In Indiamentioning
confidence: 99%
“…It should also be noted that unlike registered societies, cooperatives, or companies, 'social enterprise' does not exist in the Indian legal framework as a company format for incorporation (registration). Therefore, different actors in the social entrepreneurship ecosystem of the country, tend to consider those enterprises as social enterprise which combine the logic of market orientation and social value creation for achieving a social mission, irrespective of the legal identity of the enterprise; be it a cooperative, a trust, a society, a section 8 company, or a private limited company (Sengupta and Sahay, 2018).…”
Section: New and Renewable Energy Social Entrepreneurship In Indiamentioning
confidence: 99%
“…It is less applicable in emerging economies, where the needs are very elementary and the distinction between "social" and "commercial" is less relevant. Sengupta and Sahay [40] suggested that in those countries "the critical issues are triggered by shared necessity such as livelihood generation, poverty eradication, rural entrepreneurship, improved education, to name a few. These are addressed through group collectivism, and implemented by connecting beneficiary indigenous communities within the format of micro-institutional structures such as self-help groups."…”
Section: Social Enterprisesmentioning
confidence: 99%
“…Audio recording of pre-organized respondents' interviews and proper note-taking raise credibility of data (Hoque et al, 2017). Researcher applied note taking for interviews where either voice recording was not possible or allowed (Hoque et al, 2017;Sengupta & Sahay, 2018). To ensure rigorous research, verbatim transcription of interviews was applied (Cowton & Downs, 2015).…”
Section: Interviewingmentioning
confidence: 99%